A Comprehensive Analysis of Multi-Channel Mac and Clustering Protocols for Robust and Energy-Efficient Wireless Sensor Networks - Pawale, Sushma P.; Patil, Poornima G. (Informatika i avtomatizaciâ (Online), 2025)
Wireless Sensor Networks have become indispensable in various applications, from environmental monitoring to health tracking. As they continue to evolve, security and energy efficiency remain paramount. This analysis paper compares contemporary techniques within two significant protocol categories: Multi-Channel Medium Access Control (MAC) protocols and Cluster-Based protocols. The evaluation focuses on various channel assignment strategies and clustering methods, including static and dynamic allocation of communication resources, adaptive methodologies, and hybrid approaches, alongside strategies for selecting and rotating cluster heads, and aggregating data efficiently. Through a comprehensive examination, we highlight the limitations and potential of each approach, proposing a hybrid framework that leverages the strengths of both protocol types to enhance security and energy efficiency in Wireless Sensor Networks. Our findings suggest that integrating dynamic resource allocation with energy-efficient clustering and adaptive strategies with rotational cluster head selection could lead to more robust and efficient deployments. This analysis serves as a foundational study for future research, aiming to develop advanced hybrid protocols that address the dynamic demands of WSNs, ensuring sustainable and efficient network operations.